Water Quality and the Effectiveness of Pesticides - Frederick M. Fishel (EDIS)
Pesticide applicators do not usually blame the mix for a pest control failure. Rather, the applicator will check if the correct pesticide was chosen for the job, if the pest was misidentified, if application equipment was properly calibrated, or if there was pesticide resistance. However, pesticide applicators should be aware that water quality can play a role in the efficacy of a pesticide treatment. Some pesticides lose their effectiveness when mixed with water that contains suspended or dissolved solids. This publication discusses how water quality affects pesticide mixes. This 2-page fact sheet was written by F. M. Fishel, and published by the UF Department of Agronomy, April 2013.